Potential for CO2 emission reduction from large-scale rice fields in the Mekong Delta, Vietnam: a case study on OM4040 rice variety - Phuong Vu, Thai; Choudhury, Moharana (Frontiers in Sustainable Food Systems, 2025)
Transitioning from traditional smallholder to large-scale, mechanized rice farming offers significant potential for reducing greenhouse gas (GHG) emissions in Southeast Asia. This study assessed the environmental and economic performance of large-scale OM4040 rice cultivation in the Mekong Delta, Vietnam, using IPCC methodologies. Results showed a 15.5% reduction in CO₂-equivalent (CO₂e) emissions per ton of rice produced, driven by improved water management (e.g., alternate wetting and drying), laser-assisted land leveling, and optimized fertilizer use. Mechanized operations were found to increase fuel-based emissions, but higher yields offset this effect. Additionally, postharvest straw reuse contributed to avoiding 2.4–3.0 tons CO₂e per 10 ha per season, reinforcing circular economy principles. Economically, large-scale systems were more profitable only when land rental costs were excluded. The integration of carbon efficiency and sustainability indices provided a comprehensive evaluation of emission trade-offs. These findings support the adoption of climate-smart rice production systems and underscore the need for enabling infrastructure and land policy reforms to enhance scalability and sustainability.